Analisis IFAS dan EFAS sebagai Perencanaan Strategi untuk Melakukan Pengembangan Usaha pada PD Mie Ayam Berkah Palembang - Al Hushori; Areta Sahda Salsabila; Yusleli Herawati (Jurnal Terapan Ilmu Ekonomi, Manajemen dan Bisnis, 2024)
The purpose of writing this research is to identify a strategy for developing the most suitable business for PD Mie Ayam Berkah Palembang for its business. PD Mie Ayam Berkah is engaged in the food industry where it makes processed fresh noodles which can be used in various products such as chicken noodles, meatball noodles, curly noodles, celor noodles or dumpling skins and dim sum. The research uses the SWOT analysis method which looks at external and internal factors within the company. The results of the research that has been done show that the company's condition is very suitable for using an aggressive growth strategy (Growth oriented strategy) because from the IFAS and EFAS calculations the score is in quadrant I. The company is in a good condition to maximize the opportunities and strengths it has to Covering weaknesses also avoids threats. It was found that the conclusion is that companies can implement SO (strenghts-opportunities) strategies such as using complete licensing and good production activities to enter larger industries, optimizing the use of technology to expand consumer reach as well as financial management.